1995
DOI: 10.1155/s0962935195000585
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the adrenal gland in the anti‐inflammatory effect of polyunsaturated diets

Abstract: The effect of an n-3 (fish) and n-6 (soybean) fatty acid-rich diet on carrageenin paw oedema in rats, and the participation of adrenal gland, corticosterone and α2-macroglobulin (α2-M) in this process were studied. A significant inhibition of carrageenin oedema was observed not only in rats fed a diet rich in fish oil but also in the soybean group. α2-M was not detectable before carrageenin injection, suggesting that this putative antiinflammatory factor does not participate in the observed anti-inflammatory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
7
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
6
7
0
Order By: Relevance
“…These results are similar to other [33] in neutrophils from rats fed a soybean-rich diet. H 2 O 2 is an important citotoxic agent [34] and its lower release could contribute to the anti-inflammatory effect of the hyperlipidic diets, as observed previously [12,27] and reproduced in the present study. Some reports have shown decreased activity of superoxide-dismutase (SOD), the enzyme catalyzing H 2 O 2 formation, in plasma and in different tissues of animals treated with nY3 or nY6 PUFA-rich diets [35,36].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These results are similar to other [33] in neutrophils from rats fed a soybean-rich diet. H 2 O 2 is an important citotoxic agent [34] and its lower release could contribute to the anti-inflammatory effect of the hyperlipidic diets, as observed previously [12,27] and reproduced in the present study. Some reports have shown decreased activity of superoxide-dismutase (SOD), the enzyme catalyzing H 2 O 2 formation, in plasma and in different tissues of animals treated with nY3 or nY6 PUFA-rich diets [35,36].…”
Section: Discussionsupporting
confidence: 89%
“…Our previous [12] and present results showed that nY6 and nY3 PUFA-rich diets had a similar antiinflammatory effect and we were presently able to correlate this effect with similar changes of inflammatory mediators. The doubt remains as on the real beneficial effects of reducing the acute inflammation, since the inflammatory process is a physiological response to tissue injury, aimed at reestablishing homeostasis.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This effect was partially attributed to the elevated basal corticosterone levels induced by these diets [38,39]. Here, we show that plasma corticosterone levels did not differ in the three experimental groups.…”
Section: Discussionmentioning
confidence: 50%